2013
DOI: 10.1159/000346161
|View full text |Cite
|
Sign up to set email alerts
|

Calcifying Human Aortic Smooth Muscle Cells Express Different Bone Alkaline Phosphatase Isoforms, Including the Novel B1x Isoform

Abstract: Background: Vascular calcification, causing cardiovascular morbidity and mortality, is associated with hyperphosphatemia in chronic kidney disease (CKD). In vitro, phosphate induces transdifferentiation of vascular smooth muscle cells to osteoblast-like cells that express alkaline phosphatase (ALP). In vivo, raised serum ALP activities are associated with increased mortality. A new bone ALP isoform (B1x) has been identified in serum from CKD patients. The present study investigated the different ALP isoforms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 93 publications
1
20
0
Order By: Relevance
“…All BALP isoforms, including B1x, are also expressed in vascular smooth muscle cells (VSMCs), the calcification of which is associated with a strong increase in BALP activity level 39 . In particular, increased B1x, B/I and B2 activity could be associated with phosphate-induced vascular calcification 40 . In bone, the B1:B2 ratio differs between cortical sites (~1.7) and trabecular sites (~0.7) 35 .…”
Section: Alp Biology: Isozymes and Isoformsmentioning
confidence: 99%
See 1 more Smart Citation
“…All BALP isoforms, including B1x, are also expressed in vascular smooth muscle cells (VSMCs), the calcification of which is associated with a strong increase in BALP activity level 39 . In particular, increased B1x, B/I and B2 activity could be associated with phosphate-induced vascular calcification 40 . In bone, the B1:B2 ratio differs between cortical sites (~1.7) and trabecular sites (~0.7) 35 .…”
Section: Alp Biology: Isozymes and Isoformsmentioning
confidence: 99%
“…VSMCs exclusively express BALP in vitro 40 , most studies in human and animal models do not specify the measured TNALP isoform, which does not exclude that other isoforms could be involved in vascular calcification. The highest concentration of BALP is found in matrix vesicles shed by VSMCs 49 .…”
Section: Mechanisms Of Mineralizationmentioning
confidence: 99%
“…7 Upregulation of ALP and pyrophosphate hydrolysis is increasingly recognized as a potential mechanism of uremic vascular calcification, 27 and serum ALP predicts mortality in ESRD. 28 Even though the increased ALP activity in calcifying vascular smooth muscle cells is exclusive to bALP, 29 it is still unknown to which extent vascular calcification contributes to circulating total ALP or bALP activities. An interaction between Wnt signaling and promoters of mineralization may occur in the process of vascular calcification.…”
Section: Sclerostin and Balp: Interaction Between Wnt Signaling And Pmentioning
confidence: 99%
“…Vascular calcification involves transdifferentiation of VSMCs to an osteoblast-like phenotype, which demonstrates increased expression of BALP (163). In study II we found that BALP isoforms B/I, B1x and B2 are involved in the calcification of VSMCs in vitro (258). Furthermore, in study I we found an association of B1x with hyperphosphatemia and increased calcium×phosphate product in CKD stages 3-5, both of which are associated with CV mortality in CKD (241).…”
Section: Study IVmentioning
confidence: 69%